Microbiota, Prostatitis, and Fertility: Bacterial Diversity as a Possible Health Ally - Jenniffer Puerta Suárez; Walter D. Cardona Maya (Advances in Urology)
Background. In health, microorganisms have been associated with the disease, although the current knowledge shows that the microbiota present in various anatomical sites is associated with multiple benefits. Objective. This study aimed to evaluate and compare the genitourinary microbiota of chronic prostatitis symptoms patients and fertile men. Materials and Methods. In this preliminary study, ten volunteers have included 5 volunteers with symptoms of chronic prostatitis (prostatitis group) and five fertile volunteers, asymptomatic for urogenital infections (control group) matched by age. Bacterial diversity analysis was performed using the 16S molecular marker to compare the microbiota present in urine and semen samples from chronic prostatitis symptoms and fertile volunteers. Seminal quality, nitric oxide levels, and seminal and serum concentration of proinflammatory cytokines were quantified. Results. Fertile men present a greater variety of operational taxonomical units-OTUs in semen (67.5%) and urine (17.6%) samples than chronic prostatitis symptoms men. Chronic prostatitis symptoms men presented a higher concentration of IL-12p70 in seminal plasma. No statistically significant differences were observed in conventional and functional seminal parameters. The species diversity in semen samples was similar in healthy men than prostatitis patients, inverted Simpson index median 5.3 (5.0–10.7) vs. 4.5 (2.1–7.8, p=0.1508). Nevertheless, the microbiota present in the semen and urine samples of fertile men presents more OTUs. Less microbial diversity could be associated with chronic prostatitis symptoms. The presence of bacteria in the genitourinary tract is not always associated with the disease. Understanding the factors that affect the microbiota can implement lifestyle habits that prevent chronic prostatitis. Conclusion. Chronic prostatitis does not seem to affect male fertility; however, studies with a larger sample size are required. Our preliminary results strengthen the potential role; the greater bacterial diversity is a protective factor for chronic prostatitis.